I know that curvature for some curve $C$ defined parametrically is:

$$\kappa=\left\|{d\vec{T}\over ds}\right\|$$

Which basically is the rate at which the tangent vector to the curve changes, as the arclength of the curve changes.

In another source, I saw the definition of curvature as the following:

If $P_1$ and $P_2$ are two points on the curve, $|P_1P_2|$ is the arclength between those two points, and $\Phi$ is the limit of the angle between tangent vectors at the points $P_1$ and $P_2$ (as it goes to zero I assume), then the curvature is defined as:

$$\kappa=\lim_{|P_1P_2|\to 0}{\Phi\over |P_1P_2|}$$

Which basically means, the rate at which the angle of tangent vectors in global frame of reference changes, as the arclength of the curve changes.

I assume that this second definition can be rewritten using the notation from the first example as:

$$\kappa={d\phi\over ds}$$

Where $\phi$ is the angle between the vector tangent to the curve, and some constant global axis of reference (which could be the x axis, but realy it could be any line or vector on the same plane).

Given the second (weird in my opinion) definition of curvature, I can't see how those two definitions can be equivalent. Maybe they are not, I don't know. May be they are; if yes, how?

Also, here's a picture of the section from the book where the second definition appears in (it's not in English):

Note that the text agrees with yet another definition of curvature, which I am aware of: $\kappa=\frac1r$, where $r$ is radius of curvature.

  • 1
    $\begingroup$ Note that all of these definitions except $\frac{d\phi}{ds}$ work just as well in three dimensions as in two dimensions. To use $\frac{d\phi}{ds}$ in three dimensions you need to find the plane in which the tangent and normal vectors lie, and then you can apply that definition too. $\endgroup$ – David K Dec 27 '18 at 12:45
  • $\begingroup$ @DavidK thank you for the info, didn't even think about how that formula can be applied to three dimensions $\endgroup$ – KKZiomek Dec 27 '18 at 14:46

Let's work with the first definition. We have \begin{align} \kappa (s) &= \left\| \frac{d\vec T}{ds}(s)\right\| \\ &= \lim_{\delta s\to 0}\frac 1 {\delta s}\left\| \vec T(s + \delta s) - \vec T(s) \right\| \\ &= \lim_{\delta s \to 0} \frac 1 {\delta s} \sqrt{(\vec T(s + \delta s) - \vec T(s)).(\vec T(s + \delta s) - \vec T(s))} \\ &= \lim_{\delta s \to 0} \frac 1 {\delta s} \sqrt{\| \vec T(s + \delta s)\|^2 + \| \vec T(s) \|^2 - 2\vec T(s).\vec T(s + \delta s)}\end{align} But the curve is parameterised by arc length! So $$ \| \vec T(s + \delta s)\|^2 = \| \vec T(s)\|^2 = 1$$ and $$ \vec T(s).\vec T(s + \delta s) = \cos \Phi(s, s + \delta s),$$ where $\Phi(s, s + \delta s)$ is the angle between $\vec T(s)$ and $\vec T(s + \delta s)$.

Plugging this in, we get \begin{align} \kappa &= \lim_{\delta s \to 0} \frac 1 {\delta s} \sqrt{2 - 2 \cos \Phi(s, s + \delta s)} \\ &= \lim_{\delta s \to 0} \frac 1 {\delta s} 2 \sin \left( \frac { \Phi(s, s + \delta s) } {2}\right) \\ &= \lim_{\delta s \to 0} \frac {\Phi(s, s + \delta s)} {\delta s} \times \frac{\sin \left( \frac { \Phi(s, s + \delta s) } {2}\right)}{\frac{\Phi(s, s + \delta s)}{2}} \end{align} Clearly, $\lim_{\delta s \to 0} \Phi(s, s + \delta s) = 0$, so \begin{align} \kappa &= \lim_{\delta s \to 0} \frac {\Phi(s, s + \delta s)} {\delta s} \times \lim_{\Phi \to 0} \frac{\sin \left( \frac { \Phi } {2}\right)}{\frac{\Phi}{2}} \\ &= \lim_{\delta s \to 0} \frac {\Phi(s, s + \delta s)} {\delta s} \times 1 \\ &= \lim_{\delta s \to 0} \frac {\Phi(s, s + \delta s)} {\delta s}\end{align} which agrees with the second definition.

  • $\begingroup$ How do you get from $\sqrt{2-2\cos\Phi}$ to $2\sin\left(\frac{\Phi}{2}\right)$? $\endgroup$ – Noble Mushtak Dec 27 '18 at 0:36
  • 2
    $\begingroup$ @NobleMushtak I used $1 - \cos x = 2 \sin^2 (\tfrac x 2)$. $\endgroup$ – Kenny Wong Dec 27 '18 at 0:37

By your first statement, $T'(s)=\kappa(s)N(s)$ where $\kappa$ is the curvature and $N$ is the unit normal vector. Now, let's consider $T(s)$ and $T(s+\Delta s)$, so that we can compare the angles between tangent vectors. Now, $T(s)$, $T(s+\Delta s)$, and $N(s)$ are all unit vectors, so we can draw the following picture representing all of these vectors:

enter image description here

Here, $\Delta \theta$ is the angle between the two tangent vectors and $\Delta T=T(s+\Delta s)-T(s)$. From the diagram, we can find that $\Delta T\cdot T(s)=1-\cos \Delta \theta$ and $\Delta T\cdot N(s)=\sin d\theta$. From the x-component, we get the following equation:

$$\frac{dT}{d\theta}\cdot T(s)=\lim_{\Delta \theta\rightarrow 0}\frac{\Delta T\cdot T(s)}{\Delta \theta}=\lim_{\Delta \theta\rightarrow 0}\frac{1-\cos(\Delta \theta)}{\Delta \theta}=0$$

This was pretty obvious since $T'(s)=\kappa(s)N(s)$ is orthogonal to $T(s)$, so nothing new there. However, from the y-component, we get:

$$\frac{dT}{d\theta}\cdot N(s)=\lim_{\Delta \theta\rightarrow 0}\frac{\Delta T\cdot N(s)}{\Delta \theta}=\lim_{\Delta \theta\rightarrow 0}\frac{\sin(\Delta \theta)}{\Delta \theta}=1$$

Now, let's use chain rule to figure out what $\frac{dT}{d\theta}$ is:

$$\frac{dT}{ds}=\kappa(s)N(s)=\frac{dT}{d\theta}\frac{d\theta}{ds} \rightarrow \frac{dT}{d\theta}=\frac{\kappa(s)N(s)}{\frac{d\theta}{ds}}$$

Finally, let's plug this value for $\frac{dT}{d\theta}$ into the equation with the dot product:

$$\frac{dT}{d\theta}\cdot N(s)=1\rightarrow \frac{\kappa(s)N(s)\cdot N(s)}{\frac{d\theta}{ds}}=1\rightarrow \frac{d\theta}{ds}=\kappa(s)N(s)\cdot N(s)=\kappa(s)$$

(Note that the last step uses $N(s)\cdot N(s)=1$ since $N(s)$ is a unit vector.)

At this point, we have shown $\frac{d\theta}{ds}=\kappa(s)$, which is what we originally set out to prove. Q.E.D.

Of course, this isn't exactly a formal proof since it assumes $T(s+\Delta s)$ is in the plane spanned by $T(s)$ and $N(s)$, which isn't necessarily true. However, I think this is a fair approximation since $T'(s)=\kappa(s)N(s)$, so $T(s+\Delta s)\approx T(s)+\Delta sT'(s)=T(s)+[\Delta s\kappa(s)]N(s)$. In any case, I feel like this geometric argument gives a better visual intuition for why $|T'(s)|=\frac{d\theta}{ds}$.

  • $\begingroup$ Thank you for the answer. I accepted the other answer only because it was more straightforward, at least to me $\endgroup$ – KKZiomek Dec 27 '18 at 1:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.